Temporal and spatial variation of phytopigments in the Western part of the Ria Formosa lagoon, Southern Portugal - Pereira, M. (2012)
The spatial and temporal variation of phytoplankton pigments in the western part of Ria Formosa, Portugal, was investigated between September 2000 and July 2002. Sampling stations included the ocean boundary (Anc˜ao inlet) and two different landward boundary situations: 1) the shallow westernmost “blind end” of the lagoon (Ponte) and 2) near a main sewage outlet (Ramalhete). Nutrient concentrations were higher during the first year of sampling but were lower than those recorded in previous studies. This decrease in the concentration of nutrients was possibly the result of the 1997 relocation of the Anc˜ao inlet, which allowed better water circulation in the lagoon. Throughout this study, concentrations of chlorophyll a determined by high-performance liquid chromatography were consistently low. Inter-annual variability in the pattern of chlorophyll a concentration was observed in the form of a bimodal peak (spring/summer and autumn) between September 2000 and June 2001 and more uniformconcentrations from September 2001 until July 2002. Principal component analysis of the concentrations of all pigments did not indicate any spatial- or tidal-related variations but did show that pigment concentrations varied over time. Partial least squares analysis corroborated this temporal shift of the phytoplankton pigment abundance and composition and showed that these shifts could be linked to certain environmental variables. Fucoxanthin was the dominant accessory pigment and was strongly correlated with chlorophyll a. Other marker pigments present in lower concentrations included chlorophyll b, 19′-hexanoyloxyfucoxanthin, neoxanthin, alloxanthin, diadinoxanthin, lutein, zeaxanthin, and beta-carotene. PLS analysis was used to infer the dominant phytoplanktonic groups in the lagoon. This analysis established that diatoms and other algal groups with a similar pigment profile dominated the phytoplankton community throughout the year. Cryptophytes were the second most abundant group in the lagoon. The remaining groups, including dinoflagellates, cyanophytes, and chlorophytes, contributed much less to the total algal biomass (generally <10%).